Everything cat what kids really want to know about cats - Crisp, Marty (Chanhassen, Minn. : NorthWord Press, 2003)
Uses a question-and-answer format to present a variety of information about cats.
Did cats come from dinosaurs? -- How many breeds of cat exist day? -- Did curiosity really kill the cat? -- My cat doesn't come when I call her. Does she know her name? -- Can you teach a cat tricks? -- How much sleep does a cat need? -- Why do cats purr? -- Do cats communicate? -- Why do cats play with their food? -- Why does my cat stare at me? -- Why did my cat bring me a bird he just killed? -- How old can a cat live to be? -- Why did our old cat disappear forever? -- Why does my cat like catnip? -- Why do my cat's eyes seem to glow in photographs? -- Why do cats seem to have a hard time getting along? -- Why is my cat so picky about what he eats? -- Why doe my cat lick herself? -- Why do cats eat grass? -- Should we have our cat declawed? -- How come my cat is afraid to climb down trees? -- Do cats always land on their feet? -- Why do cats hate water? -- Do cats really have nine lives? -- Why do cats like getting on top of the fridge? -- Why is a cat's tongue rough? -- Are there any famous cats? -- Why are so many people allergic to cats? -- Is a black cat bad luck? -- Do cats like people or don't they? -- Strange cat facts -- Resources.
1010L
Keywords: Cats -- Miscellanea; Cats; Questions and answers